1996
DOI: 10.1093/oxfordjournals.humrep.a019263
|View full text |Cite
|
Sign up to set email alerts
|

Sperm chromatin anomalies can influence decondensation after intracytoplasmic sperm injection

Abstract: In this study we investigated whether morphology and chromatin anomalies in human spermatozoa can influence fertilization after intracytoplasmic sperm injection (ICSI). We examined unfertilized oocytes, using the flnorochrome Hoechst 33342, to determine whether a relationship exists between failure of fertilization and sperm chromatin quality. Sperm chromatin packaging quality was assessed using the chromomydn A 3 (CMA 3 ) fluorochrome, and the presence of DNA damage in spermatozoa, using in-situ nick translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
148
1
16

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(179 citation statements)
references
References 42 publications
14
148
1
16
Order By: Relevance
“…Any deviations in this maturation process of replacement of histones by protamines may result in poor chromatin packing and severe morphologically abnormal sperms, having a significant influence on fertilization rate [24,49]. Similarly, several studies have confirmed that poor chromatin packing may lead to sperm decondensation failures post ICSI which affects the fertilization process [50][51][52]. Furthermore, several studies have also demonstrated a strong correlation between abnormal protamination and sperm DNA fragmentation [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Any deviations in this maturation process of replacement of histones by protamines may result in poor chromatin packing and severe morphologically abnormal sperms, having a significant influence on fertilization rate [24,49]. Similarly, several studies have confirmed that poor chromatin packing may lead to sperm decondensation failures post ICSI which affects the fertilization process [50][51][52]. Furthermore, several studies have also demonstrated a strong correlation between abnormal protamination and sperm DNA fragmentation [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…The existence of an association between sperm chromatin malformation and male infertility has been repeatedly observed in humans and structural chromatin abnormalities have been found to exert negative effects both on the percentage of fertilization and on embryonic development (17,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 97%
“…During the last decade, a number of studies have shown that variable but consistent fractions of human spermatozoa not always detectable on the basis of classic morphological parameters, contain serious chromatin structural abnormalities and DNA strand breaks (12)(13)(14)(15)(16)(17)(18). The existence of an association between sperm chromatin malformation and male infertility has been repeatedly observed in humans and structural chromatin abnormalities have been found to exert negative effects both on the percentage of fertilization and on embryonic development (17,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in sperm chromatin and/or DNA damage might result in defective decondensation and a delay in the formation of the male pronucleus [53,54]. A prolonged storage of FD spermatozoa at ambient temperatures may induce such alterations and/or DNA damage.…”
Section: Discussionmentioning
confidence: 99%